A Juridical Analysis of the Elements of Intentionality and Negligence in Criminal Acts - Gogon Perdana A. Putra; Rizki Setyobowo Sangalang; Claudia Yuni Pramita (Golden Ratio of Data in Summary, 2026)
This research aims to legally examine the elements of intentionality and negligence in criminal acts as the basis for a person's criminal responsibility. The main problem in this study is how the concepts of intentionality and negligence are understood in criminal law and how they are applied in criminal justice practice. This research uses a normative legal research method with a literature study approach, namely by examining various sources such as laws and regulations, opinions of criminal law experts, and court decisions related to the research topic. The results of the study show that intentionality and negligence have quite fundamental differences in determining the fault of the perpetrators of criminal acts. Intentionality occurs when a person commits an act with the will or awareness that his act may cause consequences that are prohibited by law. Meanwhile, negligence occurs when a person is not careful or ignores the obligation to act carefully so as to cause harm or adverse consequences to others. The difference between the two elements affects the evidentiary process in court, the determination of whether or not the elements of the criminal act are met, and the severity of the criminal sanctions imposed. Therefore, the precise determination of whether an act was committed intentionally or due to negligence is essential to ensure justice, legal certainty, and the application of proportionate punishment in the criminal justice system.